Measuring indoor air quality performance in Malaysian government kindergarten - Kamaruzzaman .S.N; Razak .R.A (Penerbit UKM, 2011)
Children require good indoor environment since indoor air quality (IAQ) is very important for their growth and wellbeing. Studies around the world have found that indoor air quality affected these sensitive groups more compared to adults. In IAQ of kindergarten buildings especially in Malaysia is unknown as research on this matter is limited. The failure to identify and establish IAQ status can increase the chance of long-term and short-term health problems. Therefore, the IAQ of two government kindergartens in Malaysia was studied in this research. In these studies, all factors were considered including temperature, relative humidity (RH), airflow rate and the amount of carbon dioxide (CO2), nitrogen dioxide (NO2), formaldehyde and volatile organic compound (VOC). One case study is located in the rural area of Rembau, Negeri Sembilan and the other one is located in the city centre area of Kuala Lumpur. Measurements were taken continuously in a period of three daysin order to establish the IAQ pattern. Furthermore, a comparison with an established benchmark was conducted to identify rooms for improvement. It is anticipated that findings from this research would provide some advancement towards improving existing Malaysian policies and standards. This research could also spur other research activities concerning IAQ.